2020
DOI: 10.36740/wlek202009226
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Stone Disease With Special Regard to Drug-Induced Kidney Stones – A Contemporary Synopsis

Abstract: Kidney stone disease (nephrolithiasis; urolithiasis) is a clinical entity with long-term course and recurrence, primarily affecting mature and ageing men, involving the formation and presence of urinary stones in the kidneys and urinary tract. The pathogenesis of this disorder is complex and still not fully understood. A rare, potentially modifiable, form of kidney stone disease takes the form of drug-induced urinary stones. The aim of the review was a brief description of the classification and pathophysiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
(44 reference statements)
0
9
0
Order By: Relevance
“…Drugs regarded as being associated with an increased risk of the ability to form intrarenal crystal deposition mostly include sulphonamides, triamterene, antiretroviral drugs used in HAART therapy (delavirdine, efavirenz, nevirapine, and rilpivirine), antacids (magnesium trisilicate, aluminum hydroxide), methotrexate, quinolones (ciprofloxacin, norfloxacin), and some antibiotics (e.g., ampicillin, amoxicillin) [ 10 , 17 , 18 , 19 , 20 , 21 ]. Detailed information on the etiopathogenesis of drug-related nephrolithiasis, with particular emphasis on the specific types of drug-induced stones, is beyond the scope of this study and can be found in the detailed reviews on this subject [ 59 , 60 , 61 ]. It should be emphasized that apart from drug-induced kidney stones, developing as a result of the direct precipitation of drugs and their metabolites in the urinary tract, other indirect “metabolic, drug-related stones” may be distinguished.…”
Section: Mechanisms Of Drug Nephrotoxicity and Examples Of Offending ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Drugs regarded as being associated with an increased risk of the ability to form intrarenal crystal deposition mostly include sulphonamides, triamterene, antiretroviral drugs used in HAART therapy (delavirdine, efavirenz, nevirapine, and rilpivirine), antacids (magnesium trisilicate, aluminum hydroxide), methotrexate, quinolones (ciprofloxacin, norfloxacin), and some antibiotics (e.g., ampicillin, amoxicillin) [ 10 , 17 , 18 , 19 , 20 , 21 ]. Detailed information on the etiopathogenesis of drug-related nephrolithiasis, with particular emphasis on the specific types of drug-induced stones, is beyond the scope of this study and can be found in the detailed reviews on this subject [ 59 , 60 , 61 ]. It should be emphasized that apart from drug-induced kidney stones, developing as a result of the direct precipitation of drugs and their metabolites in the urinary tract, other indirect “metabolic, drug-related stones” may be distinguished.…”
Section: Mechanisms Of Drug Nephrotoxicity and Examples Of Offending ...mentioning
confidence: 99%
“…It should be emphasized that apart from drug-induced kidney stones, developing as a result of the direct precipitation of drugs and their metabolites in the urinary tract, other indirect “metabolic, drug-related stones” may be distinguished. The pathogenesis of the latter is associated with the induction of metabolic changes promoting lithogenesis caused by some drugs, and maybe a consequence of loop diuretics or laxatives that cause electrolyte changes, high doses of vitamin C that significantly acidify the urine, or xanthine oxidase inhibitors (allopurinol), and uricosuric compounds that cause hyperuricemia [ 60 ]. From a clinical perspective, crystal nephropathies are associated with abnormal urinalysis and urinary sediment findings, tubulopathies, and chronic kidney disease.…”
Section: Mechanisms Of Drug Nephrotoxicity and Examples Of Offending ...mentioning
confidence: 99%
“…Kidney stone pain is a severe cramping pain evoked by the movement of a stone through the urinary tract, which is augmented by the ureteral spasm and possible obstruction. The pain is usually not related to body position and is accompanied by nausea, vomiting and macro- or at least micro-hematuria and often bladder overactivity symptoms (sensation of urinary frequency and urgency) [ 52 ]. The detailed description of the pathophysiology and symptomatology of urolithiasis is out of the scope of this paper and can be found in other reviews [ 51 , 53 , 54 , 55 , 56 ].…”
Section: Urolithiasismentioning
confidence: 99%
“…According to general aetiology, one can distinguish infectious and non-infectious stones, those caused by genetic defects and those induced as a result of adverse drug reactions. On the other hand, based on the above-mentioned chemical composition, five main types of stones can be classified: calcium, struvite or magnesium ammonium phosphate, uric acid or urate, cystine and rare stones (including drug-induced ones) [ 52 , 57 ].…”
Section: Urolithiasismentioning
confidence: 99%
See 1 more Smart Citation